EXPERIENCIA PEDAGÓGICA DE PROMOCIÓN EN ALIMENTACIÓN SALUDABLE PARA ESTUDIANTES UNIVERSITARIOS - Celeghin, Adelina (Universidad Nacional del Litoral, 2020)
The academic field plays a relevant role in the creation of healthy environments and disease prevention; en this sense the university classroom becomes a space that generates opportunities. This article shows variables contemplated in the planning and execution of a pedagogical strategy oriented to nutrition, in the format of course, aimed at students of Biochemistry and Bachelor of Biotechnology of the Facultad de Bioquímica y Ciencias Biológicas, Universidad Nacional del Litoral (Santa Fe, Argentina). The subject was to provide nutritional food education to promote changes in eating habits and food choices of these students. Food Guidelines for Population of Argentina 2016 were used as thematic axis of work, promoting the active participation in learning processes. Application of recommendations from these guides was contextualized to the university field, prioritizing the realization of practical activities and their articulation with previous knowledge of these students. The results indicated that implementation of the course had a favorable impact on the construction of knowledge and skills related to food and nutrition of the participants. It is possible to conclude it would be beneficial transfering these experiences to students from other careers who are interested in the problem.